2001
DOI: 10.1590/s0037-86822001000100015
|View full text |Cite
|
Sign up to set email alerts
|

Report on the ocurrence of Angiostrongylus costaricensis in southern Brazil, in a new intermediate host from the genus Sarasinula (Veronicellidae, Gastropoda)

Abstract: Veronicellid slugs are the main intermediate hosts for Angiostrongylus costaricencis. In a rural locality in Nova Itaberaba (SC, southern Brazil) Sarasinula linguaeformis was identified as a crop pest. The parasitological examination revealed A. costaricencis infection in 43 out ot 50 slugs. The prevalence of 86% and the individual parasitic burdens are the highest sofar reported in Brazil and S. linguaeformis is the first species from the genus Sarasinula to be identified as intermediate host for A. costarice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…However, the extent to which these types of mollusc are accessible to definitive hosts may vary. A broad intermediate host range has also been reported for other Angiostrongylus species, such as A. cantonensis [ 42 , 43 ] and A. costaricensis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 94%
“…However, the extent to which these types of mollusc are accessible to definitive hosts may vary. A broad intermediate host range has also been reported for other Angiostrongylus species, such as A. cantonensis [ 42 , 43 ] and A. costaricensis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 94%
“…Mollusks from the Veronicellidae family are the main intermediate hosts in endemic areas in Costa Rica (Morera and Ash 1971), Ecuador (Morera et al 1983), Honduras (Kaminsky et al 1987), Nicaragua (Duarte et al 1992), and Brazil (Graeff-Teixeira et al 1989;Rambo et al 1997;Bonetti and Graeff-Teixeira 1998;Laitano et al 2001). However, several species belonging to other Pulmonata families were also found naturally infected (Graeff-Teixeira et al 1993;Rambo et al 1997), besides the families that were shown as potential hosts in experimental trials (Ubelaker et al 1980;Lima et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several other terrestrial molluscs have also been found to be naturally infected with this nematode in Brazil 2 , 3 , 8 , 19 and in other countries 9 , 13 , 14 . Among these species are S. linguaeformis and S. octona 2 , 3 , 8 , 9 , which, however, were not found to be infected in the present study. A possible reason for this is the lower abundance of these species in the sampled localities.…”
Section: Discussionmentioning
confidence: 99%